Phytochemical constituents and in vitro bioactivity of ethanolic aromatic herb extracts - Nurain Aziman,; Noriham Abdullah,; Zainon Mohd. Noor,; Khairusy Syakirah Zulkifli,; Wan Saidatul Syida Wan Kamarudin, (Universiti Kebangsaan Malaysia, 2012)
Phytochemical compounds, antioxidant and antibacterial activities of selected ethanolic aromatic Malaysian herbal extracts namely Persicaria hydropiper, Citrus hystrix, Murraya koenigii, Etlingera elatior, Cymbopogon citratus and Kaempferia galanga were screened and determined. Antioxidant activities were analysed using Ferric Reducing Antioxidant Power (FRAP), β-carotene bleaching and Oxygen Radical Absorbance Capacity (ORAC) assays. Disc diffusion assay was used to determine antibacterial activity against six bacteria strains. Alkaloids, flavonoids, saponins, tannins, terpenoids and steroids were detected in the herb extracts. P. hydropiper extract had the highest antioxidant activities in FRAP and ORAC assays in which 1676.67 mM TE/g EW and 11.20 mmol TE/g EW were obtained, respectively. However, M. koenigii extract showed 61.8% inhibition in β-carotene bleaching assay among samples but lower than BHA/BHT standard. M. koenigii extract showed the most effective antibacterial activity against three Gram-positive bacteria. Aromatic Malaysian herbs such as P. hydropiper and M. koenigii were found to exhibit high antioxidant and antibacterial activities.